Eastern Intellectuals and Music Culture - Khamidjonova Dilbaroy Azizbek qizi (Academia One Publishing, 2023)
The article emphasizes the unique significance of Eastern intellectuals and the cultural heritage of music in the East. It highlights the historical legacies, creative achievements, and societal impacts of Eastern intellectuals and music culture. The article defines the fundamental principles of understanding and studying culture and art history. It underscores the importance of analyzing and comprehending the Eastern intellectuals and music culture in shaping human civilization, fostering cultural changes, and achieving artistic milestones. The Eastern intellectuals and music culture play a vital role in creating distinctive cultural transformations and promoting mutual collaboration. This annotation provides a concise overview of the article and offers relevant information to pique interest in the topic.
Keywords: Eastern intellectuals; music culture; cultural analysis